Blockchain in healthcare and IoT: A systematic literature review - Endale Mitiku Adere (Array, 2022)
Blockchain technology is a highly regarded technology that possesses a plethora of exciting features. This paper analyzes trends and highlights the potential benefits of blockchain deployment in IoT and healthcare. According to the literature, blockchain technology is mostly utilized for data management operations in healthcare and IoT, specifically to improve data security, which includes data integrity, access control, and privacy preservation. In both areas, six distinct types of data security preservation strategies are applied. Additionally, publications highlight how blockchain and IoT, including health IoT, can be used in an integrative way. Three integration mechanisms were seen to accomplish this goal. These solutions range from fully integrating blockchain into data exchanges between IoT devices to using it solely for metadata storage. The most frequently covered area of IoT is a smart city, where blockchain is utilized to improve real-time data sharing, and electricity trading, and so on. Additionally, it is learned that, despite the numerous benefits of blockchain in healthcare, authors typically use it for drug supply chain management and data management purposes in order to avoid counterfeiting and empower patients with regard to their data, respectively.